Lorlatinib‐induced visual and auditory hallucinations: A case report - Jun Hakamata; Hideo Nakada; Hiroshi Muramatsu; Keita Masuzawa; Hideki Terai; Shinnosuke Ikemura; Koichi Fukunaga; Tohru Aomori (Clinical Case Reports, 2021)
Abstract Lorlatinib can cause visual and auditory hallucinations. And, it is necessary to keep in mind that hallucinations can persist even after discontinuation in patients who develop hallucinations while receiving lorlatinib.